The Big Shift: Examining Practices, Challenges and Coping Mechanisms of Teachers and Students in Transitioning to Modular Distance Learning - Mark Joseph D. Pastor; Sherwin R. Andres; Johnel R. Manarpaac (Universal Journal of Educational Research, 2022)
In response to the COVID-19 pandemic threat, the Department of Education (DepEd) established the Basic Education - Learning Continuity Plan (BE-LCP) to allow students to continue their education and teachers to conduct instruction in a safe working and learning environment. As a result, DepEd implemented the distance learning approach, including Modular Distance Learning (MDL), for the School Year 2020-2021. This paper investigated the practices, challenges, and coping mechanisms of teachers and students involved in the implementation of the MDL in Schools Division of Laoag City. This qualitative research utilized semi-structured interview guide to collect data from 20 teachers and 20 learners from elementary, junior high and senior high schools. Using the phenomenological study, data were analyzed and organized into themes. The study's major themes revealed that teachers and students began familiarizing themselves with the features of MDL but encountered challenges such as printing, distribution, and retrieval of modules, as well as monitoring of student progress on the part of the teacher and answering overloaded activities on the part of the students. They claimed, however, that they have unique coping mechanisms in dealing with the identified challenges by resolving issues independently and seeking help from family and colleagues. Finally, the Modular Distance Learning Adoption Framework (MDLAF) was developed and validated for teachers and students to effectively adopt MDL. The researchers recommended that relevant scaffolding such as capacity building, counseling and instructional support be provided to both teachers and students to effectively adopt different learning modalities such as MDL.